Potential Mechanisms and Effects of Dai Bai Jie Ethanol Extract in Preventing Acute Alcoholic Liver Injury - Niantong Xia; Hongwei Xue; Yihang Li; Jia Liu; Yang Lou; Shuyang Li; Yutian Wang; Juan Lu; Xi Chen (Current Issues in Molecular Biology)
This study investigated the protective effect of Dai Bai Jie (DBJ) extract against acute alcoholic liver injury (AALI) and elucidated its potential mechanism. The total saponin level in the DBJ extracts was measured using vanillin–chloroform acid colorimetry. To observe the preventive and protective effects of DBJ on AML-12 cells in an ethanol environment, the effective components of DBJ were identified. An alcohol-induced AALI mouse model was used to evaluate the efficacy of DBJ against AALI. For this purpose, alcohol dehydrogenase (ADH) and acetaldehyde dehydrogenase (ALDH) levels were assessed, liver function indices and oxidative and inflammatory markers were determined, and histopathological examinations were performed. Mechanistic investigations were conducted using RT-qPCR assays and immunohistochemical analysis to determine the protective effects of DBJ. The samples (DBJ-1, DBJ-2, and DBJ-3) were obtained by extracting DBJ with water, 50% ethanol, and 95% ethanol, yielding total saponin contents of 5.35%, 6.64%, and 11.83%, respectively. DBJ-3 was isolated and purified, and its components were identified by Ultra Performance Liquid Chromatography-Mass Spectrometry (UPLC-MS). DBJ-3 had the greatest effect on cell viability in an ethanol environment. Moreover, DBJ-3 reduced inflammatory infiltration, liver cell degeneration, and hemorrhage, while increasing ADH and ALDH levels in liver tissues. Additionally, DBJ-3 considerably decreased the serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol (TC), and triglyceride (TG) levels. DBJ-3 reduced malondialdehyde (MDA), reactive oxygen species (ROS), and inflammatory factors, such as tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), and interleukin 6 (IL-6), while increasing superoxide dismutase (SOD) and glutathione S-transferase (GST) activities. Furthermore, DBJ-3 significantly increased alcohol dehydrogenase 1b (ADH1B) and aldehyde dehydrogenase 2 (ALDH2) expression at the gene and protein levels within alcohol metabolism pathways and reduced the nuclear factor kappa-B (NF-κB) gene and protein levels. These findings suggest that DBJ-3 can prevent AALI by enhancing alcohol metabolism via the regulation of ADH1B and ALDH2 and the modulation of the NF-κB pathway to improve antioxidant and anti-inflammatory effects.